Recursos didácticos en la enseñanza de matemática - DAL BIANCO, Nydia; BOTTA GIODA, Rosana; CASTRO, Nora; MARTINEZ, Silvia; PEREZ BRONESKE, Mariela; PIZARRO, Rubén; PRIETO, Fabio (UNION MATEMATICA ARGENTINA, 2003)
Docentes de la Facultad de Cs.Exactas y Naturales de la U.N.L.Pampa